Coupled variable‐input LCG and clock divider‐based large period pseudo‐random bit generator on FPGA - Mangal D. Gupta; Rajeev K. Chauhan (IET Computers & Digital Techniques)
Abstract The authors present a new method for the generation of pseudorandom bits, based on coupled variable input linear congruential generator (LCG) and a clock divider. To prevent the system from falling into short‐period orbits as well as increasing the randomness of the generated bit sequences, the proposed algorithm periodically changes the seed parameters of the LCG blocks. The proposed clock divider‐based pseudorandom bit generator is compared with other LCG‐based realisations, showing great improvement. First, a clock divider is utilised for generating a maximum length of 22n pseudorandom bits for n‐bit operands size which leads to lowering the hardware cost. Secondly, it generates high‐speed random bits at a uniform clock rate with one initial clock latency. Third, the proposed technique provides good statistical properties. The proposed architecture is implemented using Verilog HDL and further prototyped on commercially available field programmable gate array (FPGA) devices Virtex‐5, Virtex‐7, and Artix‐7. The realisation of the proposed architecture in these FPGA devices accomplishes an improved data throughput and utilises minimum FPGA resources (in terms of look‐up‐tables and flip‐flops) which are compared with the existing techniques. The generated bit sequence from the experiment is further analysed briefly for sequence size and verified for randomness by using the National Institute of Standards and Technology benchmark test.